Genome wide association studies of early fitness traits in drosophila melanogaster unveil plasticity and decoupling of different aspects of phenotype - Petino Zappala, María Alejandra; Mensch, Julian; Carreira, Valeria; Soto, Ignacio; Fanara, Juan Jose (Evolutionary biology, 2024)
Great efforts have been sustained to explain the relationships between genotype and phenotype for developmental fitness traits through the study of their genetic architecture. However, crucial aspects of functional architecture influencing the maintenance of genetic variability, and thus the capacity for evolutionary change, are still unexplored. Here we performed Genome-wide Association Studies for phenotypic variability, plasticity and within-line canalization at two temperatures for Larval Developmental Time (LDT), Pupal Developmental Time (PDT), Larval Viability (LV), Pupal Viability (PV), and Pupal Height (PH) in lines derived from a natural population of Drosophila melanogaster. Results suggest changes in genetic networks linked to resource acquisition and allocation underlying variability for all traits. However, we found low genetic pleiotropy between traits and for different aspects of phenotype (means, plasticity, within-line canalization) within each trait. Their genetic bases were also temperature-specific: we found no variants showing an effect for the same trait at both temperatures. Moreover, a genetic decoupling between larval and pupal traits was confirmed, as there were no candidate variants significantly associated to phenotypic variability for the same trait across stages. We found evidence of genetic antagonistic pleiotropy for several loci affecting larval and pupal traits. The high degree of modularity at various levels would allow for the independent evolution of distinct aspects of the phenotype in different environments and ontogenetic stages. This may explain why genetic variation for these adaptive traits is not extinguished in natural populations and may entail important implications regarding evolvability.
Online veröffentlicht: 11. November 2023
Gesehen am 09.02.2026